The Effect of Chlorine Concentration on the Optical Constants of SnS Thin Films - Baghdad Science Journal (مجلة بغداد للعلوم, 2011)
Chlorine doped SnS have been prepared utilizing chemical spray pyrolysis. The effects of chlorine concentration on the optical constants were studied. It was seen that the transmittance decreased with doping, while reflectance, refractive index, extinction coefficient, real and imaginary parts of dielectric constant were increased as the doping percentage increased. The results show also that the skin depth decrease as the chlorine percentage increased which could be assure that it is transmittance related.